The acute effects of waterpipe smoking on lung function and exercise capacity in a pilot study of healthy participants. (30th July 2013) - Hawari, Feras I.; Obeidat, Nour A.; Ayub, Hiba; Ghonimat, Iyad; Eissenberg, Thomas; Dawahrah, Sahar; Beano, Hamza
Abstract: Context : Waterpipe tobacco smoking (WTS) has gained popularity, but its physiologic effects have not been extensively studied: rather, studies have focused on WTS's chronic effects or have evaluated limited respiratory/cardiac parameters. Objective : We sought to characterize in a more detailed manner the acute effects of WTS on lung function and exercise capacity. Method : We recruited 24 healthy WTS males. We used a pilot single-group pre-test (abstained from WTS for ≥48 h) post-test (within 0.5 h of a 45-min WTS session) design. We performed spirometry, diffusing lung capacity and time-limited CPE testing (CPET; cycloergometer; 2-min 20-Watt warm-up and 25-Watt increase every 2-min for 10 min). Results : Mean age was 20.4 years; Post-WTS, the following significant changes were observed: CO level increased from 3.7 ppm to 24.4; oxygen consumption decreased (from 1.86 L/min to 1.7); baseline respiratory rate increased (from 17.7 breath/min to 19.7); forced expiratory flow over the middle half of the forced vital capacity decreased (from 5.51 L to 5.29); and perceived exertion (measured by Borg scale) at mid and peak exercise increased. Baseline resting systolic blood pressure, pulse pressure, and pulse pressure product increased post-WTS (from 118.9 mmHg to 129.2; from 45.3 mmHg to 55.6; and from 9.9 mmHg/min to 11.1 post-WTS, respectively). During exercise, a decrease in oxygen pulse was observed post-WTS (from 10.89 ml/beat to 9.97), while the heart rate-oxygen consumption relationship increased post-WTS (from 3.52 beats/ml/kg to 3.91). Conclusion : Acute WTS appears to induce impairment in lung function and exercise capacity. Larger studies are warranted to further characterize the nature and extent of such impairment.